2021
DOI: 10.1021/acsami.1c07648
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of a Mg Electrode via a New Additive to Reduce Overpotential

Abstract: In non-aqueous Mg batteries, inactive adsorbed species and the passivation layer formed from the reactive Mg with impurities in the electrolyte seriously affect the Mg metal/electrolyte interface. These adlayers can impede the passage of Mg 2+ ions, leading to high Mg plating/stripping overpotential. Herein, we report the properties of a new additive, bismuth triflate (Bi(OTf) 3 ), for chlorine-free Mg electrolyte to enhance Mg plating/stripping from initial cycles. The beneficial effect of Bi(OTf) 3 can be as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…[55] In the Mg[B(Ohfip) 4 ] 2 system, Meng et al investigated an additive of bismuth(III) trifluoromethanesulfonate (Bi(OTf) 3 ), the in-situ formed Bi/Mg 3 Bi 2 film on the Mg surface would reduce the absorption of inactive species and thus enhance the resistance to passivation. [56] Parambath et al reported the addition of optimum concentration of iodine additive, which helps in the formation of a favorable, less corrosive, uniform, and stable interfacial layer. [57] The large Mg plating/stripping overpotential in the presence of polysulfide species decreased significantly after the addition of optimum concentration of iodine, which also avoids the time-consuming electrolytic conditioning behavior.…”
Section: Anode-electrolyte Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…[55] In the Mg[B(Ohfip) 4 ] 2 system, Meng et al investigated an additive of bismuth(III) trifluoromethanesulfonate (Bi(OTf) 3 ), the in-situ formed Bi/Mg 3 Bi 2 film on the Mg surface would reduce the absorption of inactive species and thus enhance the resistance to passivation. [56] Parambath et al reported the addition of optimum concentration of iodine additive, which helps in the formation of a favorable, less corrosive, uniform, and stable interfacial layer. [57] The large Mg plating/stripping overpotential in the presence of polysulfide species decreased significantly after the addition of optimum concentration of iodine, which also avoids the time-consuming electrolytic conditioning behavior.…”
Section: Anode-electrolyte Interfacesmentioning
confidence: 99%
“…In the Mg[B(Ohfip) 4 ] 2 system, Meng et al. investigated an additive of bismuth(III) trifluoromethanesulfonate (Bi(OTf) 3 ), the in‐situ formed Bi/Mg 3 Bi 2 film on the Mg surface would reduce the absorption of inactive species and thus enhance the resistance to passivation [56] . Parambath et al.…”
Section: Fluorinated Boron–centered Anionsmentioning
confidence: 99%
“…[35] The XPS analysis concludes the formation of irreversible Li x SiO y over the CC. [36][37][38][39][40] The XRD pattern of bare CC, SiO 2 @CC, and 250 h cycled SiO 2 @CC is shown in Figure 3(c). As shown in the XRD pattern, the characteristic peaks at 26°and 43°can be ascribed to (002) and (101) planes of CC.…”
Section: Postmortem Analysis Of the Symmetric Cellmentioning
confidence: 99%
“…The Zintl phase Mg 3 Bi 2 has excellent Mg-conductivity. Interestingly, using bismuth triflate (Bi(OTf) 3 ) as additive in the liquid electrolyte can be beneficial for the Mg plating/stripping, and it is attributed to the formation of a Mg-Bi interface with low interfacial resistance [ 92 ]. The drawback of Mg-Bi alloy is large volume change, hysteresis in the voltage curve and poor cycling stability.…”
Section: Low-voltage Electrodementioning
confidence: 99%